Diversity and Distribution of Endemic Flora in Pakistan - Ammad Waheed Qazi,; Zafeer Saqib,; Muhammad Zaman-ul-Haq, (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
The objective of the current research is to provide a systematic account of the variety of endemic plant species found in Pakistan, with a focus on family, distribution, and life form status. The existing research effort, which is based on a survey of the literature, field observations, and herbarium records, has identified 306 endemic plant species among 50 genera and 40 families. In accordance with an analysis of the life form or status of these plant species, herbs are dominant (n= 243 species, 80 %), while shrubs (n= 33 species, 11 %), under shrubs (n= 13 species, 4 %), trees (n= 10 species, 4 %), and grasses (n= 7 species, 2 %). The study revealed that Asteraceae is the most dominant family (n= 38 species), while Taraxacum is a dominant genus (n= 23 species). Distribution analysis revealed that the majority of species are distributed in mountainous areas of Pakistan. Khyber Pakhtunkhwa province is rich in endemism (n= 142 species, 37 %). The current study sheds light on Pakistan’s endemism situation. Further research that takes into consideration population levels and new risks is also required. The study will help policymakers in developing conservation strategies.